Peryfrazy nazw dotyczących człowieka w poezji Marii Pawlikowskiej Jasnorzewskiej - Rychter, Joanna (Slavia Occidentalis, 2014)
The article presents functional and semantic characteristics of 70 periphrases of names relating to a human being excerpted from the poetry of Maria Pawlikowska-Jasnorzewska. The study herein aims to determine the literary and cultural motives of described periphrases and the scope of their originality. The analysis of the research material shows that the periphrases of names relating to a human being perform many different functions. They mainly embellish her poems, so as to avoid repetitions and introduce information about attributes and functions of a man. Moreover, they provide semantic excess which one word synonyms lack. There are different reasons for using the described constructions. We can find periphrases deriving from Christian tradition (divine favourite ‘man’), current extra-linguistic situation (winged man ‘pilot’), or interest of the poetess in spirituality (madonna of a boring cemetery ‘Biała dama’ / ‘The White Lady’).